Graded Activity for Older Adults with Chronic Low Back Pain: Program Development and Mixed Methods Feasibility Cohort Study - Kuss, Katrin; Leonhardt, Corinna; Quint, Sabine; Seeger, Dagmar; Pfingsten, Michael; Wolf Pt, Udo; Basler, Heinz-Dieter; Becker, Annette (Pain medicine (Malden, Mass.), 2016)
Persistent pain is highly prevalent in older adults and can lead to functional limitations in activities of daily living, and to psychosocial distress. There is a lack of established active therapy programs, especially for older adults with chronic pain. To develop a graded activity program and to evaluate its feasibility within a pilot study. Phase I/phase II trial of a complex intervention. A mixed methods design was chosen to evaluate the feasibility, acceptability, and preliminary evidence of effectiveness. Several experts participated in the program development. Sixteen community-dwelling older adults (73.9 ± 5.9 years on average) with chronic low back pain and three primary care physical therapists attempted the program. Guided semi-structured interviews were conducted with all patients and therapists and used a content-analytic approach. Measurements of self-rated functional status (HFAQ), average pain (NRS), falls self-efficacy (FES-I), and catastrophizing and avoidance beliefs (CAS-D 65+) were applied at baseline and after the intervention. The interviews revealed high acceptance, satisfaction, and practicality. Besides improvements in function and pain, patients mentioned more positive attitudes towards pain, activity, and self-confidence. There was a clinically relevant increase in physical function by 20.3%, a decrease in pain intensity, and a reduction in catastrophizing and avoidance behavior. This graded activity program demonstrated feasibility and high acceptance in aged individuals and therapists. Future studies with larger samples must confirm effectiveness. The principles also appear applicable to other chronic pain conditions. The program could easily be implemented in routine primary care.